Historical importance of formation of Kazakh Khanate - Karibayev, B (Journal of history, 2020)
Author in his article pays special attention to the historical importance of formation of Kazakh Khanate. Formation of Kazakh Khanate shows that it led continuous ethnical processes in the territory of Kazakhstan to new stage and it reflects Kazakh nation as individual ethnos. Considering historical significance of formation of Kazakh Khanate from ethnical point of view, we can conclude that it influenced the completion of formation period of Kazakh nation, and gave to the ethnos, which raised ethnical processes to national level, ethno name «Kazakh». Next importance of formation of Khanate is that transforming Kazakh nation to national state. Thus, Kazakh Khanate served as original state of Kazakh nation until the end of 18th century